2023
DOI: 10.3390/hematolrep15040057
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Hematological and Hemorheological Parameters Following Mild COVID-19: A 4-Month Follow-Up Study

Janina Bros,
Lars Ibershoff,
Emily Zollmann
et al.

Abstract: Background: Coronavirus Disease 2019 (COVID-19) was described to affect red blood cells (RBC) in both severe and mild disease courses. The aim of this study was to investigate whether hematological and hemorheological changes that were previously described for COVID-19 patients after the acute infection state are still prominent after another 4 months to assess potential long-term effects. Methods: Hematological and RBC rheological parameters, including deformability and aggregation, were measured 41 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Recent studies revealed that the RBC deformability from COVID-19 patients was significantly lower than that of the control group [17,42,44,45], confirming previous findings [17]. Szewczykowski et al reported that RBCs from COVID-19 patients exhibited reduced deformability, which could hinder their passage through the capillary system and reduce oxygen transportation through the body [44].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionsupporting
confidence: 63%
See 1 more Smart Citation
“…Recent studies revealed that the RBC deformability from COVID-19 patients was significantly lower than that of the control group [17,42,44,45], confirming previous findings [17]. Szewczykowski et al reported that RBCs from COVID-19 patients exhibited reduced deformability, which could hinder their passage through the capillary system and reduce oxygen transportation through the body [44].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionsupporting
confidence: 63%
“…RBCs may also be the target of this increased oxidative stress. High levels of reactive oxygen species (ROS) can damage the RBC membrane through lipid peroxidation and protein oxidation processes [40][41][42] and promote RBC senescence through calcium accumulation and phosphatidylserine exposure [40]. The subsequent loss of membrane elasticity and RBC deformability may then affect the ability of RBCs to deliver their oxygen to tissues and favor hypoxia and thrombotic events [43].…”
Section: Influence Of Sarscov-2 On Red Blood Cell Functionmentioning
confidence: 99%
“…A change in RBC aggregation can be an important indicator of disease as well as of the course of disease progression. Therefore, the understanding of the extent of aggregation and its effect on blood rheology is important as it can be enhanced in some pathological states and diseases including infections [27], diabetes mellitus [28], cardiovascular disease [29], hypertension [30], preeclampsia [31], and other pathologies.…”
Section: Introductionmentioning
confidence: 99%